Prognostic Value of Interim 18F-DOPA and 18F-FDG PET/CT Findings in Stage 3–4 Pediatric Neuroblastoma. (January 2022) - Ko, Kuan-Yin; Yen, Ruoh-Fang; Ko, Chi-Lun; Chou, Shu-Wei; Chang, Hsiu-Hao; Yang, Yung-Li; Jou, Shiann-Tarng; Hsu, Wen-Ming; Lu, Meng-Yao
Abstract : Purpose: This retrospective study aimed to determine the prognostic value of imaging parameters derived from midtherapy 18 F-fluorodihydroxyphenylalanine ( 18 F-DOPA) and 18 F-FDG PET in pediatric patients with stage 3–4 neuroblastoma. Methods: We enrolled 32 stage 3–4 pediatric neuroblastoma patients who underwent 18 F-DOPA and 18 F-FDG PET/CT scans before and after 3 chemotherapy cycles. We measured metabolic and volumetric parameters and applied a metabolic burden scoring system to evaluate the primary tumor extent and soft tissue metastases and that of bone/bone marrow involvement. The associations between these parameters and clinical outcomes were investigated. Results: Over a median follow-up period of 47 months (range, 3–137 months), 16 patients experienced disease progression, and 13 died. After adjustment for clinical factors, multivariate Cox proportional hazard models showed that interim tumor FDG/FDOPA SUVmax (hazard ratio [HR], 5.94; 95% confidence interval [CI], 1.10–34.98) and interim FDOPA whole-body metabolic burden scores (WBMB) (HR, 7.30; 95% CI, 1.50–35.50) were significant prognostic factors for overall survival (OS). Only interim FDOPA WBMB scores (HR, 7.05; 95% CI, 1.02–48.7) were predictive of progression-free survival. Based on median cutoff values, prognosis (OS and progression-free survival) was significantly associated with an interim FDOPA WBMB score ≥21.92 (all P < 0.05) and interim tumor FDG/FDOPA (SUVmax) score ≥0.57 with poor OS ( P < 0.05). Conclusions: Our results indicate that midtreatment FDG and FDOPA PET/CT could serve as prognostic markers in stage 3–4 neuroblastoma patients.